CLASSIFICATION OF MUNANESE VERBS - La Alu (Universitas Sembilanbelas November Kolaka, 2017)
This study aimed to reveal the facts of language, especially related to the classification of Munanese verbs. Based on the semantic type of argument of Munanese verbs so can be classified into stative verbs, process verbs, and action verbs. The semantic stative verb type has at least one core argument and a maximum of two core arguments. The stative argument of a stative object is an argument that states nouns as entities that have a particular state or trait. The process verb is a verb that semantically denotes a process of entity change that occurs in the object argument (O). Argument O is tangible animate noun like human, animal, plant, and other nouns that are familiar in human life. The action verb as a verb expressing a causative event involves two events, namely: the event that causes something and the second is the result of the first event.